La civiltà del mondo antico - Ettore Ciccotti (History of Classical Scholarship, 2021)
When we launched the HCS Supplementary Volumes series in April 2020 we anticipated that it would include classic works that have long been out of print, are difficult to locate online or on the antiquarian market, and warrant further attention and discussion. This new edition of Ettore Ciccotti’s La civiltà del mondo antico is the first addition of this kind to the series. The book, published by the Istituto delle Edizioni Accademiche in 1935, is now out of copyright: we present here a searchable PDF version, preceded by an introduction by Federico Santangelo.